RECOMMENDATIONS FOR FISHERIES EXTENSION STRATEGIES IN MANGROVE MANAGEMENT ON THE DIMENSIONS OF ORGANIZING FISHERIES EXTENSION IN REMBANG SUB-DISTRICT - Nasrudin, Abdul Rohman; Pamaharyani, Luchiandini Ika; Samsidar, Samsidar; Ananda, Yosep Yuswanto Tri; Wardana, Novar Kurnia (Politeknik Kelautan dan Perikanan Dumai, 2023)
Fisheries-marine extension in mangrove forest management in Rembang has been conducted for some time, namely in 1988 until now. The problem identified is that the results of the extension program allegedly have not been implemented optimally and have never been assessed the status of its success thoroughly and especially in its sustainability status so that a fisheries extension strategy is needed. This study aims to formulate recommendations for fisheries extension strategies in mangrove management in Rembang. The analysis method used is Multi-Dimensional Scalling (MDS) through the RAPFISH (Rapid Assessment Technique for Fisheries) approach, this method is used to determine the sustainability status of fisheries extension. Sampling using purposive sampling method, with respondents from mangrove management communities and fisheries communities including fishermen, fish farmers and other fisheries business actors, as well as from the Rembang Regency Marine and Fisheries Agency. The results of this study obtained the sustainability status of fisheries extension in mangrove management in Rembang for organizing fisheries extension in Rembang which includes 5 (five) attributes of 69.89, meaning that sustainability is in the status of